ANALISIS EVALUASI OPERASIONAL ANGKUTAN UMUM DALAM KOTA TRAYEK A KABUPATEN MIMIKA - Muh. Wahid Munir Muhyiddin; Yahya Nusa (CV. Adiba Aisha Amira, 2023)
The aim of this research is to determine the causes of non-operation of public transport in the city and to determine the feasibility of public transport route A in Mimika Regency. The method used is descriptive method. The type of data used was qualitative data, and data from 3 informants were used, namely the transportation service, drivers and the community. This analysis tool uses the source triangulation method. The results of the analysis are that the causes of public transportation not operating are due to people's interest in using public transportation, the availability of public transportation vehicles and public transportation facilities and infrastructure. The feasibility of public transport route A is still worth maintaining due to new regulations and updates to public transport conditions. The hope of this research is that the existence of government programs for public transportation can increase the interest of urban public transportation users in Mimika Regency.